Joint Dynamic Bandwidth and Queue Management for Upstream SLA-Oriented QoS in Multi-Tenant, Multi-Service PONs - Ruffini, Marco (My University, 2020)
We devise a PON upstream scheduler that jointly manages intra-ONT and inter-ONT capacity across VNOs. This provides balancing between throughput and delay, providing SLA-oriented QoS supporting low latency 5G applications even in challenging multi-tenant environments.
Optical Network Design and Modeling conference (ONDM)
PUBLISHED
Keywords: PON; 5G applications; ONT; VON